1985
DOI: 10.1159/000199189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Specific Serine Protease Inhibitor on the Rat Pancreas

Abstract: Chronic oral administration of camostate, a specific serine protease inhibitor, is known to induce pancreas hypertrophy in rats. A possible influence of the protease inhibitor on the endocrine rat pancreas was studied using isolated perfused pancreas and islet incubations. The presence of camostate had no direct effect on the glucose-induced insulin release in vitro in concentrations from 1 μM to 1 mM, but enhanced the basal insulin release from islets cultured over 24 h in media containing the protease inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
3
2
0
Order By: Relevance
“…Pancreatic islets were of normal size although decreased in frequency per section as would be expected from distribution in a larger mass of exocrine tissue (data not shown). This selective effect on the exocrine pancreas is consistent with prior reports that total insulin content in the rat pancreas was not changed after camostat administration (16,35).…”
Section: Effect Of Camostat On Pancreatic Growth In Micesupporting
confidence: 92%
“…Pancreatic islets were of normal size although decreased in frequency per section as would be expected from distribution in a larger mass of exocrine tissue (data not shown). This selective effect on the exocrine pancreas is consistent with prior reports that total insulin content in the rat pancreas was not changed after camostat administration (16,35).…”
Section: Effect Of Camostat On Pancreatic Growth In Micesupporting
confidence: 92%
“…The effect of camostate or CCK treatment on the endocrine pancreas, however, has rarely been investigated, and unfortunately the results are contradictory. Thus it has been reported that insulin content in rat pancreas or isolated pancreatic islets was unchanged (Yamada, Brunstedt & Solomon, 1983;Goke et al 1985;Muller et al 1988) or insignificantly increased (Yamada, Solomon, Petersen, Levin, Lewin & Walsh, 1980). In agreement with a study by Temler and co-workers (Temler, Dormond, Simon & Morel, 1984), we, however, now observed a significant increase in pancreatic insulin content after treatment with both camostate and CCK.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, growth of the pancreas was shown to be reversible when treatment with camostate was discontinued (Muller et al 1988). In general, different groups have shown that administration of camostate or CCK increases pancreatic weight and pancreatic concentration or content of RNA and DNA, amylase, trypsin, chymotrypsin and lipase in rats (Solomon, Vanier & Morisset, 1983;Morisset, 1984;Goke, Siegel, Stockmann, Lankisch & Creutzfeldt, 1985;Sarfati, Genik & Morisset, 1985;Goke, Printz, Koop, Rausch, Richter, Arnold & Adler, 1986;Keim & Goke, 1986;Muller et al 1988;Wisner et al 1988;Schmidt et al 1989). Thus our findings on the effect of treatment with camostate or CCK on rat exocrine pancreas are well in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic administration of camostate to normal rats exerted no effects on the release of insulin (19,20). Our data on diabetic rats are in accordance with these results and put a clear contrast to our previous findings that chronic treatment of normal rats with exogenous CCK or oral cholestyramine, a bile salt sequestrant that stimulates the release of endogenous CCK, enhanced insulin release from the isolated perfused pancreas (9).…”
Section: Discussionsupporting
confidence: 89%